PELAKSANAAN SISTEM KADERISASI PARTAI GOLKAR DI KOTA PEKANBARUN TAHUN 2011-2013 - Adli Hasanuddin; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research is motivated by lex number 2 of 2011 about politic party, containing about forming of cadres as one of prereqruiment to legal politic party. Golkar Party is mass – party and has 30 years on Indonesian politic. Party Golkar dominate has spread to all Indonesian region. However, in recent years a decline in the number of cadres, specially in Pekanbaru City.This qualitative research with indepht interview and documentation as data collection techniques. This research armed to explain forming of cadres implementate on Golkar Party in Pekanbaru 2011-2013. The theory used Political Party theory, Political education and forming of cadres system. Forming of cadres system is necessary for Political Party, cause forming or cadres is process to made human resources to be responsible leader.The result is, Golkar Party in Pekanbaru has not be able to implement forming of cadres as well. In 2011-2013, Golkar Party in Pekanbaru only do one education and training in 2013, that is orientation of fungsionaris. Education and traning carrie out least once a year. Consolidation is other of forming of cadres activity. Consolidation is also held once on 2012, which is this activity not appropriate to the concept. Whereas, in 2011 nothing forming of cadres activity undertaken .Keyword: Golkar, Political Party, Forming of cadres